Evaluation of Clinical Efficacy of Smart Insulin for Diabetes Management: A Systematic Review - Chintan Doshi (Indian Journal of Medical Biochemistry)
Background: Diabetes mellitus is a chronic metabolic disorder that requires lifelong management. Traditional insulin therapy can be limited by its short duration of action, requiring multiple daily injections, and its potential to cause hypoglycemia. Smart insulin, also known as glucose-responsive insulin, is a new class of insulin that can automatically adjust its activity in response to changes in blood glucose levels. Objectives: 1. To evaluate the efficacy of smart insulin in improving glycemic control in patients with diabetes mellitus. 2. To assess the safety of smart insulin, including the risk of hypoglycemia and other adverse events. 3. To compare the efficacy and safety of smart insulin with traditional insulin therapy. Materials and methods: 1. Search strategy: A comprehensive literature search will be conducted using major electronic databases, including PubMed, Embase, Scopus, Web of Science, and Cochrane Library. 2. Inclusion criteria: Randomized controlled trials (RCTs) and observational studies that evaluate the efficacy and safety of smart insulin in patients with diabetes mellitus. 3. Exclusion criteria: Studies that do not report outcomes of interest, studies with a sample size of less than 10 participants, and studies that are not published in English. 4. Data extraction: Two reviewers will independently extract data from included studies using a standardized data extraction form. 5. Risk of bias assessment: The Cochrane Risk of Bias Tool will be used to assess the risk of bias in included RCTs. 6. Data synthesis: A meta-analysis will be conducted to pool the results of included studies. Outcomes: 1. Primary outcome: Change in HbA1c levels from baseline to follow-up. 2. Secondary outcomes: a. Incidence of hypoglycemia. b. Change in fasting plasma glucose levels. c. Change in body weight. d. Patient-reported outcomes, such as quality of life and treatment satisfaction. Registration: PROSPERO CRD42022312346.